Electrochemical Oxidation Using BDD Anodes Combined with Biological Aerated Filter for Biotreated Coking Wastewater Treatment - C. R. Wang; Z. F. Hou; M. R. Zhang; J. Qi; J. Wang (Journal of Chemistry)
Coking wastewater is characterized by poor biodegradability and high microorganism toxicity. Thus, it is difficult to meet Grade I of Integrated Wastewater Discharge Standard of China by biological treatment technology; specifically, COD cannot meet above standard due to containing refractory organics. A novel coupling reactor, electrochemical oxidation using BDD anodes and biological aerated filter (BAF), has been developed for carbon and nitrogen removal from biotreated coking wastewater, focusing on COD, BOD5, NH4+-N, and NO3--N removal on operation over 90 days with average effluent value of 91.3, 9.73, 0.62, and 13.34 mgL−1, respectively. Average value of BOD5/COD and BOD5/NO3--N was enhanced from 0.05 to 0.27 and from 0.45 to 1.21 by electrochemical oxidation, respectively, with average energy consumption of 67.9 kWh kg−1 COD. In addition, the refractory organics also were evidently mineralized in the unit based on the data of the three-dimensional fluorescence spectra. Meanwhile, its effluent provided excellent substrate for biological denitrification in BAF. At hydraulic retention time (HRT) of 13.08 h, about 12 mgL−1  NO3--N was depleted through denitrification, and it mainly occurred at top of 0.25 m height of BAF. Therefore, it is feasible to apply the coupling reactor for biotreated coking wastewater treatment and achieve desirable effluent quality.